Environmental Impact Assessment on the Development and Operation of Type B Terminal in Bontang City - Tukimun Tukimun; Diyat Susrini Widayanti; Wahyu Mahendra Trias; Riz Anugrah; Kumarul Zaman (LPPM of NAROTAMA UNIVERSITY, 2023)
Purpose: The Type B Terminal is critical for improving the area's connectivity and accessibility, particularly in Bontang City and its surroundings. The principles of equality, ecological balance, resilience, sustainable development, viability, and connectivity will guide the terminal's construction and operation. The effects on environmental components must be evaluated, and appropriate countermeasures must be implemented to ensure the project's long-term viability. Design/methodology/approach: The impacts and countermeasures of the terminal in Gunung Telihan Village, West Bontang District, Bontang City, East Kalimantan Province were determined using a qualitative descriptive method. The matrix method was used to determine the significant impacts during the pre-construction, construction, and operational stages. The structure and operation are expected to have seven effects on the physical environment components, including a reduction in air quality, an increase in noise intensity, a decrease in surface water quality, a disruption in smooth and safe traffic, damage to existing roads, specific waste handling (unloading), and the generation of domestic solid and liquid waste. Findings: At the same time, three components must be evaluated when implementing countermeasures: disruption of smooth and safe traffic, generation of domestic solid and liquid waste, and handling of specific waste (building demolition) to mitigate the impacts. Paper type: Research paper